2021
DOI: 10.3390/biom11020300
|View full text |Cite
|
Sign up to set email alerts
|

Challenges and Perspective in Integrated Multi-Omics in Gut Microbiota Studies

Abstract: The advent of omic technology has made it possible to identify viable but unculturable micro-organisms in the gut. Therefore, application of multi-omic technologies in gut microbiome studies has become invaluable for unveiling a comprehensive interaction between these commensals in health and disease. Meanwhile, despite the successful identification of many microbial and host–microbial cometabolites that have been reported so far, it remains difficult to clearly identify the origin and function of some protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 81 publications
0
36
0
1
Order By: Relevance
“…It has been studied in more than 300 clinical and over 1000 scientific studies. Lactobacillus reuteri (Daliri, Ofosu, Xiuqin, Chelliah, & Oh, 2021) and Lactobacillus johnsonii (Davoren et al., 2019) are two novel LAB probiotics that have potential for the development of functional dairy products.…”
Section: Probioticsmentioning
confidence: 99%
“…It has been studied in more than 300 clinical and over 1000 scientific studies. Lactobacillus reuteri (Daliri, Ofosu, Xiuqin, Chelliah, & Oh, 2021) and Lactobacillus johnsonii (Davoren et al., 2019) are two novel LAB probiotics that have potential for the development of functional dairy products.…”
Section: Probioticsmentioning
confidence: 99%
“…Shotgun metatranscriptomics can answer the question of what microbes are doing “right then” in an ecosystem ( Franzosa et al., 2014 ). Analyzing their RNA provides clues to determining their metabolic activities in response to stress and how such alteration in metabolic activity influences host phenotypes in healthy or diseased conditions ( Daliri et al., 2021 ).…”
Section: Influences Of the Gut Microbiome And Analysis Approachesmentioning
confidence: 99%
“…Metabolomics involves the study of metabolites in a biological sample as well as the exploration of microbe-derived therapeutic products. A targeted or untargeted approach can be used ( Daliri et al., 2021 ). The former is used to study metabolites in specific pathways associated with a particular disease, while the latter measures as many metabolites in the sample as possible ( Commisso et al., 2013 ; Vignoli et al., 2019 ).…”
Section: Influences Of the Gut Microbiome And Analysis Approachesmentioning
confidence: 99%
“…Several studies have reported on manufacturing foods with increased riboflavin, such as bread, pasta, and soy milk, using LAB that overproduces riboflavin [18][19][20], and reports on improving riboflavin deficiency using fermented soy milk rich in riboflavin are also available [16]. There have also been studies on the treatment of gastrointestinal diseases using riboflavin overproducing LAB [25][26][27]. However, there is not enough evidence on whether consuming these foods can resolve riboflavin deficiency, and there is no research on whether riboflavin is absorbed in vivo by directly ingesting riboflavinoverproducing LAB.…”
Section: Introductionmentioning
confidence: 99%